BRAND DESAIN MELALUI MEDIA KOMUNIKASI VISUAL SEBAGAI SARANA PROMOSI DAN INFORMASI PADA DINAS PARIWISATA KABUPATEN SEMARANG - AYYUB HAMDANU BUDI NURMANA MULYANA SLAMET; Sugiarto Sugiarto (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
With the choice of tourists increasing and giving each other the concept of trust, with almost similar values, this makes tourists more curious and confused. The influence of quality, quality, price and persuasive persuasion will influence tourists continuously in weighing which one is the best, which is more in his heart. However, on the other hand, this condition actually shows the weakness of the Tourism Office that tourists are a determining factor for the future of one of the tourist attractions, with the confidence of tourists supporting the economy of the people in tourist sites, especially under the Semarang Regency Tourism Office. Currently the Semarang Regency Tourism Office uses posters and advertises through yellowpages as a medium for delivering information, from the promotional methods carried out there are still obstacles, including the use of posters and through yellowpages advertising, which is very limited in terms of size and information to be conveyed. Therefore, it requires a promotional media that is able to provide complete information about tourism profiles to potential tourists